Attitudes Toward Degrees - Katz, Graham (Proceedings of Sinn und Bedeutung, 2019)
Degree modifiers of the type exemplified in the sentence “She was frustratingly late” are analyzed. These modifiers, which indicate that a propositional attitude – here frustration – holds with respect to the degree associated with the predicate – here lateness, are shown to have certain monotonicity entailments which are absent from simple adverbial attitude reports such as “Frustratingly, she was 10 minutes late.” These entailments account for an interesting puzzle concerning the semantics of the degree modifiers which arises when standard analyses of attitude predicates are combined with standard accounts of degree modification.